Preparedness and response to COVID-19 in Saudi Arabia: Building on MERS experience - Abdullah A. Algaissi; Naif Khalaf Alharbi; Mazen Hassanain; Anwar M. Hashem (Elsevier, 2020)
Nearly four months have passed since the emergence of the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2), which caused the rapidly spreading Coronavirus Disease 2019 (COVID-19) pandemic. To date, there have been more than 2.3 million confirmed cases and more than 160,000 deaths globally caused by COVID-19. Chinese health authorities, where the virus emerged, have taken prompt strict public health measures to control and prevent the spread of the outbreak. In Saudi Arabia, unprecedented precautionary strict measures were applied to prevent virus entry to the country or to mitigate its impact when it arrives. Here, we review the response of Saudi Arabia to COVID-19 pandemic and how did the experience learned from the Middle East respiratory syndrome coronavirus (MERS-CoV) epidemic since 2012 has helped the country to be better prepared for the current COVID-19 pandemic. We also discuss the country readiness, improvement in research and development, and the unprecedented rapid precautionary measures that have been taken by the Saudi government thus far.